From Silos to Synergy: Collaborative Laboratories and the Transformation of Knowledge Production - Santos, José M. R. C. A.; Brandão, Ana Sofia (Emerging Science Journal, 2025)
The increasing societal importance of cutting-edge science and technology calls for a closer examination of public policies' influence on the evolving dynamics of knowledge production and transfer. This focus is especially pertinent in peripheral economies such as Portugal, where persistent structural challenges include the limited integration of highly qualified human resources within the economy. The purpose of this research is to investigate how the knowledge coproduction and transfer dynamics of ‘Collaborative Laboratories’ (CoLABs), a new form of intermediary organization in Portugal, differ from those of more traditional science-industry interface set-ups, in the Portuguese context. This research employed a deductive, quantitative, multiple-case, cross-sectional design, utilizing scientific publications as collaboration indicators and applying Social Network Analysis to map and analyze the knowledge coproduction and transfer networks of CoLABs in Portugal, comparing them to Technology Centers. The results reveal that CoLABs prioritize the creation of flexible collaboration networks and the broad coproduction and dissemination of knowledge. CoLABs are found to function as value-occupying hub organizations and serve as crucial bridging entities and are characterized by high connectivity, diverse collaboration, and cohesive research and innovation communities. The need for public agencies and CoLAB governance structures to devise strategies to enhance communication and collaboration within the CoLAB network is highlighted. This is the first study to investigate CoLABs as a new form of intermediary organization in Portugal, specifically examining how their knowledge coproduction and transfer dynamics differ from more traditional science-industry interface set-ups in the Portuguese context.